1996
DOI: 10.1523/jneurosci.16-23-07619.1996
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Levels Increased by Activation of Metabotropic Glutamate Receptors Correlate with Visual Plasticity

Abstract: We have investigated the cAMP level increased by stimulation of metabotropic glutamate receptors (mGluRs) in cat visual cortex during development. The cAMP level increases activated by the general mGluR agonist (1S,3R)-1-amino-1,3-cyclopentane-dicarboxylic acid (ACPD) were closely correlated with the critical period for ocular dominance plasticity in both light- and dark-reared animals. Activation of either group I or group II mGluRs increased the cAMP level. Group II mGluR activation also reduced the forskoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 52 publications
(72 reference statements)
0
37
1
Order By: Relevance
“…Activation of the InsP 3 /Ca 2ϩ pathway by group I mGluRs in neurons has been extensively characterized (1). In addition, stimulation of these receptors has been shown to increase cAMP levels during early developmental stages in the hippocampus (37), during the critical period in the visual cortex (38), and in neuronal cultures (39), although the molecular mechanisms underlying this effect are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the InsP 3 /Ca 2ϩ pathway by group I mGluRs in neurons has been extensively characterized (1). In addition, stimulation of these receptors has been shown to increase cAMP levels during early developmental stages in the hippocampus (37), during the critical period in the visual cortex (38), and in neuronal cultures (39), although the molecular mechanisms underlying this effect are less well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Second, NMDAR signaling may lead to the inhibition of phosphodiesterases that modulate basal levels of cAMP. Third, G-protein-coupled metabotropic glutamate receptors may stimulate AC via release of ␤␥ subunits, or activation of protein kinase C (Reid et al, 1996). Fourth, crosstalk with the extracellular signal-regulated kinase (ERK) pathway, which is also required for visual cortical plasticity (Di Cristo et al, 2001), may lead to PKA activation.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…and this value is significantly different from DCG IV-induced LTD depicted in Figure 1 A ( p Ͻ 0.05). Reid et al (1996), Schoepp et al (1996), and Sortino et al (1996) suggested that group II mGluRs can increase cAMP levels. Therefore finally, in additional cells, we tested the effect of selective PKA inhibitor KT5720.…”
Section: Dcg Iv-induced Ltd Requires Activation Of Postsynaptic Pkcmentioning
confidence: 99%